2011
DOI: 10.1161/circulationaha.111.020727
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen I Knockdown Human Embryonic Stem Cells Induce Host Ignorance and Achieve Prolonged Xenogeneic Survival

Abstract: Background-Although human embryonic stem cells (hESC) have enormous potential for cell replacement therapy of heart failure, immune rejection of hESC derivatives inevitably would occur after transplantation. We therefore aimed to generate a hypoantigeneic hESC line with improved survival characteristics. Methods and Results-Using various in vivo, nonischemic, hindlimb xenotransplant models (immunocompetent and defined immunodefective mouse strains) as well as human in vitro T-cell and natural killer (NK)-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The progressive immune response towards ESC was characterized by generation of alloreactive Th1 cells, development of donor ESC-specific antibodies [33] and accelerated rejection of a subsequent ESC infusion [34,35]. Similarly, transplantation of hESC to wild-type, natural killer (NK) cell deficient or B cell deficient mice led to vigorous T-cell-mediated rejection and failure to develop teratoma [8,36,37]. Although further studies are clearly required, these findings suggested that early predictions of low immunogenicity may ultimately proved premature, reflecting the inevitable complexities of the xenogeneic models used, rather than novel properties of the PSC cells per se.…”
Section: Key Pointsmentioning
confidence: 99%
“…The progressive immune response towards ESC was characterized by generation of alloreactive Th1 cells, development of donor ESC-specific antibodies [33] and accelerated rejection of a subsequent ESC infusion [34,35]. Similarly, transplantation of hESC to wild-type, natural killer (NK) cell deficient or B cell deficient mice led to vigorous T-cell-mediated rejection and failure to develop teratoma [8,36,37]. Although further studies are clearly required, these findings suggested that early predictions of low immunogenicity may ultimately proved premature, reflecting the inevitable complexities of the xenogeneic models used, rather than novel properties of the PSC cells per se.…”
Section: Key Pointsmentioning
confidence: 99%
“…While undifferentiated PSCs have some degree of immune privilege [106], their differentiated progeny including cardiomyocytes are immunogenic and clearly evoke an immune response in allogeneic recipients [16,107]. A number of exotic solutions to this problem have been proposed including the creation of isogeneic PSCs by somatic cell nuclear transfer [108], the creation of “universal donor” PSC lines via HLA engineering [109,110], and the induction of tolerance via bone marrow microchimerism [111,112]. Because iPSCs can be genetically matched to their recipient, they represent another theoretical solution to this problem, although the creation of “customized” autologous iPSC therapies would likely present a new set of practical hurdles in terms of scalability, economics, and regulatory burden.…”
Section: Remaining Hurdles To Translationmentioning
confidence: 99%
“…Recently, MHC-I knock-down has been reported to be effective in profoundly reducing hESC rejection (Deuse et al , 2011), the residual MHC-I expression in MHC-silenced cells being expected to provide suffi cient protection against the negligible response of human natural killer cells to hESC challenge (Drukker et al , 2002).…”
Section: Immunogenicitymentioning
confidence: 99%